Pengalaman stres pesakit semasa menerima ventilasi mekanikal yang berpanjangan di unit rawatan rapi(ICU), Hospital Universiti Sains Malaysia (HUSM) - Hartini, Abu Bakar@ Hassan (PPSP, Universiti Sains Malaysia, 2007)
Introduction : Many studies conducted in the west show prolonged stay and ventilation in the ICU settings result ini physical and psychological stress. This include invasive treatment modalities, difficulties in breathing, sleep disturbances and communication problems. This study dwells with important aspect in nursing field which becoming more challenging today. Objectives : The objective of this study is to determine the stressful experience among patients who was managed in the Intensive Care Unit in extended period. Method : This is a cross-sectional study involving 60 patient who were admitted in the ICU and could recall the event during the stay. Patient selection was based on convenience sampling. Those who were selected need to give verbal and written consent. They were brief on the nature the study, the objectives, procedures and and their rights. Subsequently they were given a set of questionnaires. The questionnaires were than complied and recorded in a database using a computer software known as SPSS version 12.01. The data were analysed using descriptive analysis. The association between demographic factors and stressful experience was tested using chi square. Results : Endotracheal tube is regarded to be more stressful experience compared to ICU stay. Overall, stressful experience was less than unstressful experience. Furthermore, p-value was also not significant with other demographic factors. Conclusion : This findings will be used as a basis to upgrade the services ini the ICU settings. Further detailed research in every aspect of stressful experience or possibly stressful event will be justified in order to expedite recovery as well as patients quality of life.